ARAÚJO, Ana Carvalho Ziller; CARVALHO, Ernesto Ignacio de & CARELLI, Vincent (orgs.). Vídeo nas Aldeias 25 anos: 1986-2011. - Lopes, André (Revista de Antropologia, 2014)
ARAÚJO, Ana Carvalho Ziller; CARVALHO, Ernesto Ignacio de & CARELLI, Vincent (orgs.). Vídeo nas Aldeias 25 anos: 1986-2011. Olinda/ pe, Vídeo nas Aldeias, 2011, 256 pp.